Brushing Hegel Against the Grain: On Katrin Pahl, Tropes of Transport: Hegel and Emotion - Boldyrev, Ivan (Stasis, 2016)
Book review: Katrin Pahl, Tropes of Transport: Hegel and EmotionEvanston, Illinois: Northwestern University Press, 2012, 356pp., ISBN 978-0810127845